Perceptions of Arabic Students in Using the Sevima Edlink Application: Empirical Experience from Universitas Islam Negeri Imam Bonjol Padang - Husna, Ilya; Azkiya, Hidayati; Musalwa, Musalwa; Ikhlas, Al; Refdianti, Afrina (Jurnal Pendidikan Agama Islam Al-Thariqah, 2024)
This research aims to investigate Arabic students' perceptions of the use of the SEVIMA Edlink platform in learning process. The object of this research was 161 students of the Arabic Language Education and Arabic Language and Literature UIN Imam Bonjol Padang study program. The method used in this research is a mix method. The results of the investigation in this research show that, in terms of use, this platform is easy to use, and students think that this platform provides good access to lecture materials and assignments. Other findings show that the level of interaction between students and lecturers on this platform is still lacking. However, overall, the majority of students are satisfied with the use of SEVIMA Edlink in their lectures and recommend it to other students. The researcher recommends to investigate lecturers' perceptions of using the SEVIMA Edlink platform and also strategies for developing it in higher education.